Akupresur Untuk Meningkatkan Daya Tahan Tubuh - Ros Endah Happy Patriyani (Jurnal Empathy Pengabdian Kepada Masyarakat, 2022)
Background: One of the complementary modalities that can be done independently by everyone to increase endurance is acupressure. Doing acupressure on certain acupuncture points on the body will activate the circulation of vital energy thereby increasing the body's natural immunity. This community service activity aims to increase knowledge about how to increase endurance and skills in performing acupressure using fingers, or other body parts, or blunt-tipped tools. Method: Activities are carried out by means of lectures, discussions, demonstrations, and simulations. The sample in this Community Service is 30 PKK mothers from RT 3 RW 9 Purbayan, Baki, Sukoharjo. The training was held from 15.30-17.00 WIB. Participants did 2x each acupuncture point. Knowledge data was collected using a questionnaire in the form of 15 closed questions to find out the participants' knowledge before and after the activity and a checklist on how to do acupressure at 5 points to measure skills in doing acupressure. Results: an increase in the average value of participants' knowledge was obtained from 58.26 to 88.56. The results of observations on how to do acupressure at 5 points were carried out using a checklist with the result that 90% of participants were able to do acupressure according to Standard Operating Procedures(SPO). Conclusion: Community Service Activities have a positive effect on increasing knowledge about body resistance and acupressure skills in participants. The results of this activity are expected to help participants and their families improve their immune system.